An Analysis of The Impact of Work Life Balance and Flexible Arrangements on The Welfare of Banking Sector Employees - Heriyana Heriyana; Risa Andriani; Taty Noorhayati; Diddo Adding Adove; Rola Nurul Fajria (Universitas Pahlawan Tuanku Tambusai, 2026)
The banking sector is known as an industry with high levels of work pressure, long working hours, and strict performance target demands, which have the potential to reduce the level of welfare of its employees. This study aims to analyze the effect of Work-Life Balance (WLB) and Flexible Work Arrangements (FWA) on employee welfare in the banking sector. This quantitative research with a causal associative explanatory design involved 210 commercial bank employees selected using a purposive sampling technique. Primary data were collected through the distribution of structured questionnaires with a 5-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS software. The results of the analysis indicate that Work-Life Balance and Flexible Work Arrangements have a positive and significant effect on employee welfare in the banking sector, both partially and simultaneously. These findings emphasize the importance of implementing work-life balance policies and work flexibility to reduce stress levels, prevent burnout, and improve the psychological and financial well-being of workers in the financial services industry. Keywords: Work-Life Balance, Flexible Work Arrangements, Employee Welfare, Banking Sector, SEM-PLS.